2019
DOI: 10.3390/cancers12010098
|View full text |Cite|
|
Sign up to set email alerts
|

Histone 2A Family Member J Drives Mesenchymal Transition and Temozolomide Resistance in Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is the most aggressive brain tumor and has a poor prognosis and is poorly sensitive to radiotherapy or temozolomide (TMZ) chemotherapy. Therefore, identifying new biomarkers to predict therapeutic responses of GBM is urgently needed. By using The Cancer Genome Atlas (TCGA) database, we found that the upregulation of histone 2A family member J (H2AFJ), but not other H2AFs, is extensively detected in the therapeutic-insensitive mesenchymal, IDH wildtype, MGMT unmethylated, or non-G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…H2AFJ was reported to be over-expressed in some cancers [7][8][9]11], and interrogation of the Cancer Genome Atlas (TCGA) database showed that prostate and breast cancer expressed high levels of H2AFJ mRNA (Figure 4, left panel). H2AFJ RNA was also highly expressed in many cancer cell lines derived from glandular tissues such as the breast, pancreas, lung, colorectum, thyroid, esophagus, stomach, and prostate according to the Broad Cancer Cell Line Encyclopedia (CCLE) (Figure 4, right panel).…”
Section: H2aj Is a Marker Of Luminal Breast And Prostate Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…H2AFJ was reported to be over-expressed in some cancers [7][8][9]11], and interrogation of the Cancer Genome Atlas (TCGA) database showed that prostate and breast cancer expressed high levels of H2AFJ mRNA (Figure 4, left panel). H2AFJ RNA was also highly expressed in many cancer cell lines derived from glandular tissues such as the breast, pancreas, lung, colorectum, thyroid, esophagus, stomach, and prostate according to the Broad Cancer Cell Line Encyclopedia (CCLE) (Figure 4, right panel).…”
Section: H2aj Is a Marker Of Luminal Breast And Prostate Cancer Cellsmentioning
confidence: 99%
“…H2A.J has been implicated in the expression of inflammatory genes in senescent fibroblasts [5,6]. H2A.J over-expression has also been implicated in luminal-B breast cancer tumorigenesis [7,8] and in the chemotherapeutic resistance of colorectal [9], hepatic [10], and glioblastoma cancers [11]. We performed a global survey of H2A.J expression in human and mouse tissues to obtain initial indications regarding potential tissue-specific functions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 117 ] Other studies demonstrated that the histone 2A family member J (H2AFJ) is involved in TMZ resistance and MES transformation through NF‐ κ B and STAT3‐dependent signaling. [ 118,119 ] GSCs can induce an immunosuppressive nature in TAM through mTOR‐dependent regulation of STAT3 and NF‐ κ B activity. [ 120 ] Our group recently reported that GSCs with MES subtype can force PN cells to switch into a MES phenotype by means of extracellular vesicles (EVs), [ 121 ] a small vesicle released by practically every cell.…”
Section: Therapy Resistance and Clinical Implications Of Mesenchymal mentioning
confidence: 99%
“…Furthermore, they showed that inhibition of STAT3 increased TMZ-induced G 0 -G 1 arrest and decreased cyclin D1 expression compared to TMZ alone. A more recent study pointed to histone 2A family members (H2AFs) as components of nucleosomes crucial for gene regulation in the host [ 133 ] . This group found that H2AFJ, but not other H2AFs, is commonly found and upregulated in mesenchymal-type GBM tumors, compared to its expression in normal tissues derived from GBM patients [ 28 ] .…”
Section: Key Molecular Pathways In Temozolomide Resistancementioning
confidence: 99%